Proceedings of 37th International Cosmic Ray Conference — PoS(ICRC2021) 2021
DOI: 10.22323/1.395.0457
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Cosmic Ray Ensembles originated nearby the Sun

Abstract: Cosmic Ray Ensembles (CRE) are yet not observed groups of cosmic rays with a common primary interaction vertex or the same parent particle. One of the processes capable of initiating identifiable CRE is an interaction of an ultra-high energy (UHE) photon with the solar magnetic field which results in an electron pair production and the subsequent synchrotron radiation. The resultant electromagnetic cascade forms a very characteristic line-like front of a very small width (∼ meters), stretching from tens of tho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
0
0
Order By: Relevance
“…Particle cascades initiated by UHE photons in the geomagnetic field have been studied using Monte Carlo simulations [21,22]. Similarly, propagation of UHE photons in the solar magnetosphere was also studied using Monte Carlo simulations by [23][24][25][26]. The results showed that the photon disintegrates, giving rise to extended cascades comprising of thousands of spatially correlated secondary particles which lose energy through synchrotron emission.…”
Section: Search For Uhe Photonsmentioning
confidence: 99%
“…Particle cascades initiated by UHE photons in the geomagnetic field have been studied using Monte Carlo simulations [21,22]. Similarly, propagation of UHE photons in the solar magnetosphere was also studied using Monte Carlo simulations by [23][24][25][26]. The results showed that the photon disintegrates, giving rise to extended cascades comprising of thousands of spatially correlated secondary particles which lose energy through synchrotron emission.…”
Section: Search For Uhe Photonsmentioning
confidence: 99%